IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL, AND MEDIUM ENTITIES (SAK EMKM) - Saputri, Apriliya Eka (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2025)
This study aims to analyze the financial statement presentation of the Micro, Small, and Medium Enterprise (MSME) Pizza-Q in implementing the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). It explores how Pizza-Q prepares its financial statements and whether they comply with SAK EMKM, the challenges faced during the preparation process, and the solutions to overcome these challenges. This research uses a qualitative method to provide a comprehensive description of how Pizza-Q presents its financial statements in accordance with SAK EMKM. The results of the study indicate that the owner of the MSME is motivated to prepare financial reports and apply standards based on the prevailing regulations. This reflects the entrepreneur's willingness to grow and develop the business.